Lipiodol Absorption Test with a Chloroform Solution Indicator - Immanuel Mustadjab; Muzief Munir (Paediatrica Indonesiana, 1982)
The incidence of fat malabsorption in neonates with diarrhea was investigated from July until November 1975, by the lipiodol absorption test which used a chloroform solution indicator.In our study we got the following results:- 45.9% out of 24 neonates with diarrhea had fat malabsorption.This broke down to 9.1% with mild, 63.6% with moderate and 27.3% with severe fat malabsorption.- 45% of the patients had mild dehydration and 50% had severe dehydration with fat malabsorption.Usually there is a correlation between the microscopic examination of stools and the lipiodo/ absorption test.The employment of the lipiodol absorption test with a chloroform solution indicator is simpler and easier than with an amylum solution indicator.